Carbonyl sulfur removal from blast furnace gas: Recent progress, application status and future development. (November 2022) - Wang, Yifan; Ding, Long; Long, Hongming; Xiao, Junjun; Qian, Lixin; Wang, Hongtao; Xu, Chunbao (Charles)
Abstract: Carbonyl sulfide (COS), a poisonous and harmful gas, is found in industrial gas products from various coal-firing processes. The emission of COS into the atmosphere contributes to aerosol particles that affect the global climate, posing a risk to climate change and population health. In recent years, the total amount of anthropogenic COS emissions has increased significantly, resulting in the prominent COS pollution problem and becoming a vital environmental issue. This review summarizes the research progress of removing COS from industrial gases. According to the characteristics of different industrial gas products, the COS removal mechanism and influence factors, as well as the advantages and disadvantages for various methods, are discussed, including oxidation, absorption/adsorption, hydrogenation, and hydrolysis. Although COS emission control technologies have attracted widespread attention, the progress of application in blast furnace gas purification has been extremely slow, insufficient and sporadic. To fill the gap, this work provides a timely review on blast furnace gas characteristics and application process of various methods for removing COS from blast furnace gas with varying compositions, and their challenges and future development. This work aims to provide guidance on how effective processes and techniques for removal of COS from blast furnace gas can be developed. This review emphasizes the desirability of direct COS removal from blast furnace gas compared to expensive terminal desulfurization technologies. Furthermore, the development of a new process for low-temperature COS removal from blast furnace gas based on a dual-functional catalyst of hydrolysis/adsorption is advocated. Graphical abstract: Image 1 Highlights: The advances in removing COS from industrial gases are reviewed. Various methods for COS removal are discussed. The challenges and opportunities of COS removal are summarized. Removal of COS directly from blast furnace gas is advocated. Hydrolysis/adsorption bifunctional catalysts demonstrate promise in removal of COS.